2017
DOI: 10.1111/1742-6723.12759
|View full text |Cite
|
Sign up to set email alerts
|

Auckland regional emergency medicine trainee mentoring uptake survey

Abstract: Many EM trainees in Auckland want a formal mentoring system and would like a mentor. Appropriate mentor-mentee matching through a formalised voluntary system, with adequate mentor training, may enable the Auckland region to develop a suitable mentoring programme for EM trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In preparation for a survey on local mentoring needs we conducted a literature review of mentoring in emergency medicine. We found essentially no empirical evidence to support mentoring in our setting . However, as clinicians we recognise that a lack of empirical evidence does not equate to a lack of benefit, nor discredit the need for something …”
mentioning
confidence: 69%
“…In preparation for a survey on local mentoring needs we conducted a literature review of mentoring in emergency medicine. We found essentially no empirical evidence to support mentoring in our setting . However, as clinicians we recognise that a lack of empirical evidence does not equate to a lack of benefit, nor discredit the need for something …”
mentioning
confidence: 69%
“…A 2012 online survey of 565 surgical trainees in the UK found that 49% had a mentor and of those that did not, 89% wanted one . A 2016 study of 61 ACEM trainees in a large New Zealand teaching hospital found that 95% of respondents wanted a mentoring programme, yet 75% were not currently in a mentoring relationship . Many UK colleges have implemented formal mentoring programmes, including the Royal Colleges of Surgeons, Psychiatrists, Radiologists, Obstetricians and Gynaecologists, while an Australian review of medical disciplines in 2013 found that mentoring had been officially embraced by the respective colleges of anaesthetics, pathology, radiology, dental surgery, rural and remote medicine…”
Section: Mentoring In Medicinementioning
confidence: 99%
“…11 A 2016 study of 61 ACEM trainees in a large New Zealand teaching hospital found that 95% of respondents wanted a mentoring programme, yet 75% were not currently in a mentoring relationship. 12…”
Section: Mentoring In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well-recognised benefits of mentoring, research indicates that a large proportion of the mentoring needs of doctors are not adequately met (Chen et al, 2016;Frank-Bertoncelj et al, 2014;Han et al, 2014;Nicholls et al, 2017;Sambunjak et al, 2006;Soto & Walsh, 2019). To counteract the unmet need, hospitals and institutions have developed formal mentoring programs.…”
Section: Introductionmentioning
confidence: 99%